Vacuolar sucrose cleavage prevents limitation of cytosolic carbohydrate metabolism and stabilizes photosynthesis under abiotic stress. (28th September 2018) - Weiszmann, Jakob; Fürtauer, Lisa; Weckwerth, Wolfram; Nägele, Thomas
Abstract : Stabilization of central carbohydrate metabolism plays a key role in plant stress response. Carbohydrates are substrate for numerous metabolic and stress‐responsive reactions and have been shown to be involved in diverse signalling processes on a whole‐plant level. Regulation of enzymatic sucrose synthesis and degradation is well‐known to be central to many stress‐related processes as it significantly impacts stress tolerance. Leaf sucrose metabolism involves sucrose cleavage by invertases and ATP‐consuming resynthesis catalysed by hexokinase and sucrose phosphate synthase. These reactions establish a metabolic cycle. To study the physiological role of sucrose cycling, a kinetic model was developed to simulate dynamics of subcellular sugar concentrations in Arabidopsis thaliana under combined cold and high‐light stress. Model simulation revealed that subcellular reprogramming of invertase‐driven sucrose cleavage varies substantially between natural accessions of Arabidopsis which differ in their cold tolerance levels. A stress‐induced shift of sucrose cleavage from the cytosol into the vacuole could only be observed for the tolerant accession while the susceptible accession increased the cytosolic proportion of sucrose cleavage. Under stress, reduction in vacuolar invertase activity significantly affected maximum quantum yield of photosystem II and CO2 assimilation rates. While wild‐type plants circumvented a limitation of sucrose cleavage by increasing vacuolar invertase activity, mutant plants were not able to compensate their deficiency of vacuolar by cytosolic activity. Consequently, the capacity for cytosolic hexose generation was lower than for enzymatic hexose phosphorylation suggesting a role of vacuolar invertase activity in preventing a limitation in cytosolic hexose metabolism under stress. Enzymes: Invertase, EC 3.2.1.26 ; Hexokinase, EC 2.7.1.1 . Abstract : Regulation of sucrose biosynthesis and degradation plays a central role in abiotic stress response of plants. Invertases catalyse the hydrolytic cleavage of sucrose to release glucose and fructose. Combining subcellular carbohydrate analysis and kinetic modelling, our study indicates that vacuolar invertase prevents stress‐induced limitation of cytosolic hexose metabolism and stabilizes photosynthesis.